Effects of Hematocrit of the Sealed Blood on the Leakage Characteristics of Blood Cell Component and Plasma Component in a Mechanical Seal - Jun Tomioka (Japanese Society of Tribologists, 2016)
The purpose of this study is to find out the effects of hematocrit of the sealed blood on the leakage characteristics of blood cell components and plasma components in a mechanical seal, which separates blood from cooling water. The hematocrit was controlled to 0, 10, 20, 30 and 40%. Each component leakage was obtained by measuring the increase in the potassium ion concentration and the sodium ion concentration in the cooling water. It was revealed that each component leakage became larger with the increase of the hematocrit in the three-hour measurement. When changing the hematocrit from 20% to 30%, the volume percentage of the blood cell component leakage remarkably increased by 7.7 times. The friction characteristics of the mechanical seal under blood sealing and the hemolytic properties of the sealed blood were also studied. There is a typical trend under the mixed lubrication condition where the friction torque decreased with each of the sealed blood as the rotational speed increased. The hemolytic index of the sealed blood after the measurement experiments of the blood leakage increased with the increase of the hematocrit.